xxxxxxxxxx
List = [[0,1,2], [3,4,5]]
comp_list = [item for sublist in List for item in sublist]
print(comp_list)
xxxxxxxxxx
l = [[1, 2], [3, 4], [5, 6, 7]]
flat_list = [item for sublist in l for item in sublist]
# flat_list = [1, 2, 3, 4, 5, 6, 7]
xxxxxxxxxx
# idiomatic python
# using itertools
import itertools
list_of_list = [[1, 2, 3], [4, 5], [6]]
chain = itertools.chain(*images)
flattened_list = list(chain)
# [1, 2, 3, 4, 5, 6]
xxxxxxxxxx
my_list = [[1], [2, 3], [4, 5, 6, 7]]
flat_list = sum(my_list, [])
print(flat_list)
xxxxxxxxxx
my_list = [[1], [2, 3], [4, 5, 6, 7]]
flat_list = [num for sublist in my_list for num in sublist]
print(flat_list)
xxxxxxxxxx
regular_list = [[1, 2, 3, 4], [5, 6, 7], [8, 9]]
flat_list = [item for sublist in regular_list for item in sublist]
print('Original list', regular_list)
print('Transformed list', flat_list)
xxxxxxxxxx
flattened = [val for sublist in list_of_lists for val in sublist]
xxxxxxxxxx
from functools import reduce
my_list = [[1], [2, 3], [4, 5, 6, 7]]
print(reduce(lambda x, y: x+y, my_list))